2006
DOI: 10.1677/erc.1.01126
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of novel agents for prostate cancer chemoprevention

Abstract: Despite advances in the understanding of prostate cancer (PCa) growth and development, it is still the leading incidence of cases and the second leading cause of mortality due to cancer in men. The problem of early diagnosis compounded with the emergence of androgen independence during commonly used anti-androgen therapy of PCa, have been discouraging for optimal therapeutic response. Recently, many chemopreventive agents, including silibinin, inositol hexaphosphate, decursin, apigenin, acacetin, grape seed ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 230 publications
3
118
0
1
Order By: Relevance
“…3A); densitometric analysis accounted for almost 50% reduction (data not shown). The other important regulator of CDKs is a family of their inhibitory proteins known as CDK inhibitors that bind to CDK-cyclin complex and negatively regulate CDK activity (2,4). Based on our observed cell cycle arrest effect of gallic acid, we next assessed whether this agent also modulated the levels of CDK inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…3A); densitometric analysis accounted for almost 50% reduction (data not shown). The other important regulator of CDKs is a family of their inhibitory proteins known as CDK inhibitors that bind to CDK-cyclin complex and negatively regulate CDK activity (2,4). Based on our observed cell cycle arrest effect of gallic acid, we next assessed whether this agent also modulated the levels of CDK inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Condensed tannins are known as proanthocyanidins, which are the most abundant flavonoids present in GSE. 13 GSE demonstrated the strongest antioxidant effects and free radical scavenging ability 14 as well as being anti-inflammatory, 15 anticancer, 16 antibacterial 17 ; it has platelet aggregation inhibiting and metal chelating properties 18 and vasodilatory, immunostimulating, antiallergic, antiviral activates 19 ; it reduced plasma cholesterol in animals fed a high cholesterol diet and that may reduce risk of atherosclerosis. 20 Recently, GSE has been marketed as dietary supplement and advocated for its multiple beneficial properties.…”
Section: Introductionmentioning
confidence: 99%
“…20 Recently, GSE has been marketed as dietary supplement and advocated for its multiple beneficial properties. 14 Based on the reported antioxidant and antiinflammatory properties and vasodilatory action of polyphenolic compounds that exist in GSE, the hypothesis was made that GSE could attenuate oxidative stress, renal damage, and atherosclerosis induced by GM and HC. Therefore, the aim of this study was to investigate the renoprotective effect of GSE against oxidative stress, renal damage, and atherosclerosis induced by GM and HC in rats through the assessment of kidney biochemical parameters and lipid profile.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that sequence variations in the TLR4 gene and TLR6-TLR1-TLR10 gene cluster are associated with prostate cancer risk (54)(55)(56). However, the functional role of TLR variants in the growth and development of prostate cancer remains to be established (57).…”
Section: The Mechanism Of Selenium In Prostate Cancermentioning
confidence: 99%
“…Among the Cdks, Cdk2, Cdk4, Cdk6 and Cdk1 are the most frequent kinases that are deregulated in prostate cancer (57). Cdks can be activated by association with cyclin, by phosphorylation of its T-loop threonine by Cdk-activating kinase and by dephosphorylation of threonine 14/tyrosine 15 by cdc25 phosphatase (66).…”
Section: Cell Cycle Pathway Cyclins Cyclin-dependent Kinases (Cdks) mentioning
confidence: 99%